OM/Claudio_Maggioni_4/Claudio_Maggioni_4.md

10 KiB


title: Homework 4 -- Optimization Methods author: Claudio Maggioni header-includes:

  • \usepackage{amsmath}
  • \usepackage{hyperref}
  • \usepackage[utf8]{inputenc}
  • \usepackage[margin=2.5cm]{geometry}
  • \usepackage[ruled,vlined]{algorithm2e}
  • \usepackage{float}
  • \floatplacement{figure}{H}
  • \hypersetup{colorlinks=true,linkcolor=blue}

\maketitle

Exercise 1

Exercise 1.1

The lagrangian is the following:

L(X,\lambda) = f(X) - \lambda \left(c(x) - 0\right) = -3x^2 + y^2 + 2x^2 +
2(x+y+z) - \lambda x^2 - \lambda y^2 -\lambda z^2 + \lambda =$$$$= (-3 -\lambda)x^2 + (1-
\lambda)y^2 + (2-\lambda)z^2 + 2 (x+y+z) + \lambda$$

The KKT conditions are the following:

First we have the condition on the partial derivatives of the Lagrangian w.r.t.
$X$:

$$\nabla_X L(X,\lambda) = \begin{bmatrix}(-3-\lambda)x^* + 1\\(1-\lambda)y^* +
1\\(2-\lambda)z^* + 1\end{bmatrix} = 0 \Leftrightarrow
\begin{bmatrix}x^*\\y^*\\z^*\end{bmatrix} =
\begin{bmatrix}\frac1{3+\lambda}\\-\frac1{1-\lambda}\\-\frac{1}{2-\lambda}\end{bmatrix}$$

Then we have the complementarity condition:

$$c(X) = {x^*}^2 + {y^*}^2 + {z^*}^2 - 1 = 0 \Leftrightarrow \|X^*\| = 1$$

$$\lambda^* c(X^*) = 0 \Leftarrow c(X^*) = 0 \text{ which is true if the above
condition is true.}$$

Since we have no inequality constraints, we don't need to apply the KKT
conditions realated to inequality constraints.

## Exercise 1.2

To find feasible solutions to the problem, we apply the KKT conditions. Since we
have a way to derive $X^*$ from $\lambda^*$ thanks to the first KKT condition,
we try to find the values of $\lambda$ that satisfies the second KKT condition:

$$c(x) = \left( \frac{1}{3+\lambda} \right)^2 + \left( -\frac{1}{1-\lambda} \right)^2 +
\left(-\frac{1}{2-\lambda}\right)^2 - 1 =
\frac{1}{(3+\lambda)^2} + \frac{1}{(1-\lambda)^2} + \frac{1}{(2-\lambda)^2} - 1 =$$$$=
\frac{(1-\lambda)^2(2-\lambda)^2 + (3+\lambda)^2(2-\lambda)^2 +
(3+\lambda)^2
(1-\lambda)^2 - (3+\lambda)^2 (1-\lambda)^2 (2-\lambda)^2}{(3+\lambda)^2
(1-\lambda)^2 (2-\lambda)^2} = 0
\Leftrightarrow$$$$\Leftrightarrow
(1-\lambda)^2(2-\lambda)^2 + (3+\lambda)^2(2-\lambda)^2 +
(3+\lambda)^2
(1-\lambda)^2 - (3+\lambda)^2 (1-\lambda)^2 (2-\lambda)^2 = 0
\Leftrightarrow$$$$\Leftrightarrow
(\lambda^4 - 6\lambda^3 + 13\lambda^2 - 12\lambda + 16) +
(\lambda^4 + 2\lambda^3 - 11\lambda^2 - 12\lambda + 36) +
(\lambda^4 + 4\lambda^3 -  2\lambda^2 - 12\lambda + 9)$$$$
+ (\lambda^6 -14\lambda^4 +12\lambda^3 +49\lambda^2 -84\lambda + 36) = $$$$
=-\lambda^6 +17\lambda^4 -12\lambda^3 -49\lambda^2 +48\lambda +13 = 0
\Leftrightarrow $$$$ \Leftrightarrow
\lambda = \lambda_1 \approx -0.224 \lor
\lambda = \lambda_2 \approx -1.892 \lor
\lambda = \lambda_3 \approx 3.149 \lor
\lambda = \lambda_4 \approx -4.035$$

We then compute $X$ from each solution and evaluate the objective each time:

$$X = \begin{bmatrix}\frac1{3+\lambda}\\-\frac1{1-\lambda}\\
-\frac{1}{2-\lambda}\end{bmatrix}
\Leftrightarrow$$$$\Leftrightarrow
X = X_1 \approx \begin{bmatrix}0.360\\-0.817\\-0.450\end{bmatrix} \lor
X = X_2 \approx \begin{bmatrix}0.902\\-0.346\\-0.257\end{bmatrix} \lor
X = X_3 \approx \begin{bmatrix}0.163\\0.465\\0.870\end{bmatrix} \lor
X = X_4 \approx \begin{bmatrix}-0.966\\-0.199\\-0.166\end{bmatrix}$$

$$f(X_1) = -1.1304 \;\; f(X_2) = -1.59219 \;\; f(X_3) = 4.64728 \;\; f(X_4) =
-5.36549$$

## Exercise 1.3

To find the optimal solution, we choose $(\lambda_4, X_4)$ since $f(X_4)$ is the
smallest objective
value out of all the feasible points. Therefore, the solution to the
constrained minimization problem is:

$$X \approx \begin{bmatrix}-0.966\\-0.199\\-0.166\end{bmatrix}$$

# Exercise 2

## Exercise 2.1

To reformulate the problem, we first rewrite the explicit values of $G$, $c$,
$A$ and $b$.

We first define matrix $G$ as a set of 9 unknown variables and $c$ a set of 3
unknown variables:

$$G = \begin{bmatrix}g_{11}&g_{12}&g_{13}\\g_{21}&g_{22}&g_{23}\\
g_{31}&g_{32}&g_{33}\end{bmatrix} \;\;\; c =
\begin{bmatrix}c_1\\c_2\\c_3\end{bmatrix}$$

We then define $f(x)$ in the following way:

$$f(x) = \frac12 \cdot \begin{bmatrix}x_1&x_2&x_3\end{bmatrix}
\begin{bmatrix}g_{11}&g_{12}&g_{13}\\g_{21}&g_{22}&g_{23}\\
g_{31}&g_{32}&g_{33}\end{bmatrix} \begin{bmatrix}x_1\\x_2\\x_3\end{bmatrix}
- \begin{bmatrix}c_1&c_2&c_3\end{bmatrix}\begin{bmatrix}x_1\\x_2\\x_3\end{bmatrix}
=$$$$=x_1^2 \cdot \frac{g_{11}}{2} + x_2^2 \cdot \frac{g_{22}}{2} +
x_3^2 \cdot \frac{g_{33}}{2} +
\left(\frac{g_{12} + g_{21}}{2}\right) x_1 x_2
+ \left(\frac{g_{13} + g_{31}}{2}\right) x_1 x_3 +
\left(\frac{g_{23} + g_{32}}{2}\right) x_2 x_3 + c_1 x_1 + c_2 x_2 + c_3 x_3$$

Then, we equal this polynomial to the given one, finding the following values
and constraints for the coefficients of $G$ and $g$:

$$\begin{cases}g_{11} = 3 \cdot 2 = 6 \\
g_{22} = 2.5\cdot 2 = 5 \\
g_{33} = 2 \cdot 2 = 4 \\
c_1 = -8 \\
c_2 = -3 \\
c_3 = -3 \\
g_{13} + g_{31} = 1 \cdot 2 = 2 \\
g_{12} + g_{21} = 2 \cdot 2 = 4 \\
g_{23} + g_{32} = 2 \cdot 2 = 4 \end{cases}$$

As it can be seen by the system of equations above, we have infinite possibility
for choosing the components of the $G$ matrix that are not on the main diagonal.
Due to personal taste, we choose those components in such a way that the
resulting $G$ matrix is symmetric. We therefore obtain:

$$G = \begin{bmatrix}6&2&1\\2&5&2\\1&2&4\end{bmatrix} \;\;\;
c = \begin{bmatrix}-8\\-3\\-3\end{bmatrix}$$

We perform a similar process for matrix $A$ and vector $b$

$$Ax = b \Leftrightarrow
\begin{bmatrix}a_{11}&a_{12}&a_{13}\\a_{21}&a_{22}&a_{23}\end{bmatrix}
\begin{bmatrix}x_1\\x_2\\x_3\end{bmatrix} =
\begin{bmatrix}b_1\\b_2\end{bmatrix} \Leftrightarrow
\begin{cases}a_{11}x_1 + a_{12}x_2 + a_{13}x_3 = b_1\\a_{21}x_1 + a_{22}x_2 +
a_{23}x_3 = b_2\end{cases}$$

To make this system match the given system of equality constraints, we need to
set the components of $A$ and $b$ in the following way:

$$\begin{cases}a_{11} = 1\\a_{12} = 0\\a_{13} = 1\\a_{21} =
0\\a_{22}=1\\a_{23}=1 \\b_1 = 3 \\b_2 = 0\end{cases}$$

Therefore, we obtain the following $A$ matrix and $b$ vector:

$$A = \begin{bmatrix}1&0&1\\0&1&1\end{bmatrix} \;\;\; b = \begin{bmatrix}3\\0\end{bmatrix}$$

Then, using these $G$, $c$, $A$ and $b$ values, and using the quadratic
formulation of the problem written on the assignment
sheet, the problem is restated in the desired new form.

## Exercise 2.2

The lagrangian for this problem is the following:

$$L(x, \lambda) = \frac12\langle x, Gx\rangle + \langle x, c \rangle - \lambda
(Ax - b) =$$$$= \begin{bmatrix}x_1&x_2&x_3\end{bmatrix}
  \begin{bmatrix}6&2&1\\2&5&2\\1&2&4\end{bmatrix}
    \begin{bmatrix}x_1\\x_2\\x_3\end{bmatrix} +
      \begin{bmatrix}x_1&x_2&x_3\end{bmatrix}
        \begin{bmatrix}-8\\-3\\-3\end{bmatrix} - \lambda
          \left(\begin{bmatrix}1&0&1\\0&1&1\end{bmatrix}
            \begin{bmatrix}x_1\\x_2\\x_3\end{bmatrix} -
              \begin{bmatrix}3\\0\end{bmatrix}\right)$$


The KKT conditions are the following:

First we have the condition on the partial derivatives of the Lagrangian w.r.t.
$X$:

$$\nabla_x L(x, \lambda) = Gx + c - A^T \lambda =
\begin{bmatrix}
6 x_1 + 2 x_2 +   x_3 - 8 + \lambda_1\\
2 x_1 + 5 x_2 + 2 x_3 - 3 + \lambda_2\\
1 x_1 + 2 x_2 + 4 x_3 - 3 + \lambda_1 + \lambda_2\end{bmatrix} = 0$$

Then we have the conditions on the equality constraint:

$$Ax - b = 0 \Leftrightarrow \begin{bmatrix}x_1 + x_3\\x_2 + x_3\end{bmatrix} =
  \begin{bmatrix}3\\0\end{bmatrix}$$

Then we have the complementarity condition:

$$\lambda^T (Ax - b) = 0 \Leftarrow Ax - b = 0 \text{ which is true if the above
condition is true.}$$

Since we have no inequality constraints, we don't need to apply the KKT
conditions realated to inequality constraints.

# Exercise 3

## Exercise 3.1

The lagrangian of this problem is the following:

$$L(x, \lambda) = c^T x - \lambda^T (Ax - b) - s^T x$$

The KKT conditions are the following:

1. The partial derivative of the lagrangian w.r.t. $x$ is 0:
   $$\nabla_x L(x, \lambda, s) = c - A^T \lambda - s = 0 \Leftrightarrow A^T \lambda
   + s = c$$
2. Equality constraints hold:
   $$Ax - b = 0 \Leftrightarrow Ax = b$$
3. Inequality constraints hold:
   $$x \geq 0$$
4. The lagrangian multipliers for inequality constraints are non-negative:
   $$s \geq 0$$
5. The complementarity condition holds (here considering only inequality
   constraints, since the condition trivially holds for equality ones): $$s^T x
   \geq 0$$

## Exercise 3.2

We define the dual problem is the following way:

$$\max b^T \lambda \;\; \text{ s.t. } \;\; c - A^T \lambda \geq 0
\Leftrightarrow A^T \lambda \leq c \;$$

We then introduce a slack variable $s$ to find the equality and inequality
constraints:

$$\max b^T \lambda \;\; \text{ s.t. } \;\; A^T \lambda + s = c \; \text{ and
}\; s \geq 0$$

To convert this maximization problem in a minimization one (in order to achieve
standard form), we flip the sign of
the objective and we find:

$$\min - b^T \lambda \;\; \text{ s.t. } \;\; A^T \lambda + s = c \; \text{ and
}\; s \geq 0$$

We then compute the Lagrangian of the dual problem:

$$L(\lambda, x, s) = -b^T \lambda + x^T (A^T \lambda + s - c) - x^T s  = - b^T
\lambda + x^T (A^T \lambda - c)$$

The KKT conditions are the following:

1. The partial derivative of the lagrangian w.r.t.\ $\lambda$ is 0: $$\nabla_{\lambda}
   L(\lambda, x) = - b^T + x^T A^T = 0 \Leftrightarrow Ax = b$$
2. Equality constraints hold: $$A^T \lambda + s = c$$
3. Inequality constraints hold: $$c - A^T \lambda \geq 0 \Leftrightarrow s \geq
   0 \;\;\; \text{ using 2.\ to find that } s = c - A^T \lambda$$
4. The lagrangian multipliers for inequality constraints are non-negative: $$x
   \geq 0$$
5. The complementarity condition holds (here considering only inequality
   constraints, since the condition trivially holds for equality ones): $$x^T s
   \geq 0 \Leftrightarrow s^T x \geq 0$$

Then, if we compare the KKT conditions of the primal problem with the ones above
we can match them to see that they are identical:

- 1.\ from the dual is identical to 2.\ from the primal;
- 2.\ from the dual is identical to 1.\ from the primal;
- 3.\ from the dual is identical to 4.\ from the primal;
- 4.\ from the dual is identical to 3.\ from the primal;
- 5.\ from the dual is identical to 5.\ from the primal.

Therefore, the primal and the dual problem are equivalent.